Multi-Scale joints roughness characterization using wavelet and shear modeling - Sharifzadeh, Mostafa; Mehri, S.; Mirzaeian, Y.
Mechanical behavior prediction of rock joints is very important in the rock mechanics. Many models have been proposed to predict the mechanical behavior of joints at which lack of correct evaluation of effective roughness coefficient has been the most important shortage. In this research, each of the upper and lower profiles of joint surfaces is considered as a 2-dimensional wave. Then, multi-scale decomposition based on wavelet theory has been applied studying on asperities. Upper and lower profiles have been combined to produce a composite surface having asperities characteristics of both joint surfaces. Each of the composed wave components (roughness and undulation) has been characterized with statistical quantity of arithmetic mean deviation (Ra). This procedure of characterizing for 2-dimensional waves has been easily extended to 3-dimensional joint surfaces. Conformity in the results of shear and dilation modeling and laboratory tests satisfactorily verifies success of the proposed procedure.